(3JMQjQ GdCUhds - (3ceGd GdOjf eMeO Hf YHO GdhGMO Hf YHO GdMejO Hf GdgeGe GdSjhGSj GdEScfOQj, GdceGd Hf GdgeGe,J (B861 (3g` s
(3ChdgG (B:s
(3hHYO aEfi HYO Gf UQaJ WGFaI ef GdYeQ ddfXQ ai WQjbi GdMfajI hGdTGaYjI ai GdGUhd NWQ di Cf GcJH cJGHkG eaUMkG hQJHJg HYO JSejJg HGdJMQjQ Ydi ebOeI ai GdebOeGJ hKdGK ebGdGJ ai GdeHGOF s
(3BNQgG (B:s
(3hdGTc ai JhcjOgG ai GdhLGA GcQeJg dcfg de jLF hde fMUhG GdeKd HGdYGWaI EP dGaQb s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B134s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3CUhd Gdabgs